Role of preoperative assessment of serum sodium in transurethral resection of prostate to avoid transurethral resection of prostate syndrome: a comparative study - Gamit, Bhavesh; Thakkar, Nimesh Bharatkumar (International Surgery Journal, 2020)
Background: Transurethral resection of prostate syndrome (TURP) syndrome is an iatrogenic complication caused by absorption of the irrigating fluid which is used to distend the bladder during surgery. Methods: A total of 100 patients with benign prostatic hyperplasia (BPH) were taken for study. Study was done in tertiary care centre in Gujarat from January 2016 to December 2017. They were evaluated pre-operative and post-operative for sodium concentration. Results: In this study most of the patients i.e. 32 were seen in age group 61- 65 years.31% cases have developed hyponatremia out of 6% were having serum sodium level <125 mEq/l. 56% of cases were having prostate gland <40 cc. In 70% cases, TURP was completed within 60 minutes, while 30% cases required more than 60 minutes time. 13 were seen in age group 51 to 60 years, means 40.62% patients of this age group (13/32) and 12 patients were seen in age group 71-80 years, means 52.17% patients of this age group (12/23) were having post-operative hyponatremia. Out of 31 patients, 20 patients (64.52%) were having prostate size more than 60 cc and 11 patients (35.48%) were having prostate size between 46 to 60 cc. Conclusions: From present study, it is concluded that electrolyte derangement occurs in older patients, with larger amount of tissue and longer time of resection and higher volume of irrigation fluid. It was also noticed that chances of electrolyte derangement are higher in patients with co-morbid conditions.